ANEMIA IBU HAMIL TRIMESTER II SEBAGAI FAKTOR RISIKO BERAT BAYI LAHIR RENDAH (BBLR), LAHIR PREMATUR DAN LAHIR MATI DI KABUPATEN SUKOHARJO JANUARI-OKTOBER 2011 - Wibowo, Yudhi; TB, Rahayujati; AP, Wisnuwijoyo (MANDALA of Health, 2014)
Sukoharjo, in 2010, the Infant Mortality Rate (IMR) 66.7 % occurred in the neonatal period with the largest direct cause of LBW was 26% , others 22 % , 17 % asphyxia , 12% congenital anomalies and pneumonia 9% . In 2010, prevalence of maternal anemia was 3.92 %, but the number of Low Birth Weight (LBW) and infant mortality actually increased . This research is to prove that maternal anemia in the second trimester as risk factors of LBW , premature birth and stillbirth . Analytic observational study with a retrospective cohort study design . Subjects were all pregnant women who have given birth in the month of January to October 2011 and had no history of anemia in Trimester I. The chi-square test to examine the association of maternal anemia in the second trimester with outcomes . Binary logistic regression was used to control potential confounding variables . There are 236 women giving birth who meet the inclusion and exclusion criteria , 72 (30.5 %) were exposed group (anemic trimester 2) and 164 (69.5 %) including the unexposed group (non-anemic trimester 2). Maternal anemia in the second trimester who delivered LBW (61.9 %) , premature birth (91.2 %) and stillbirths (75 %) . Maternal anemia in the second trimester was 3.7 times increased risk for LBW (p < 0.01 , RR = 3.7 ( 2.73 to 4.99 ) , increased the risk more than 23 times for the incidence of preterm birth (p < 0,01 , RR = 23.5 (7.44 to 74.50) , but not statistically significant (p=0.08 ) and RR = 6.83 (0.72 to 64.58) for the incidence of stillbirth . After controlling for potential variable modifier is a history of LBW , preterm birth and history of the ANC , maternal anemia in the second trimester increase more than 4 times the risk for LBW with Adjusted RR = 4.43 (2.73 to 7.18) and p < 0.01 . LBW and preterm birth is more common in pregnant women with anemia TM2 so important to have checks Haemoglobine in pregnant women according to gestational age and follow-up.